The Internalisation of Character Values as a Means of Strengthening the Personal Competencies of Primary School Teacher Training Students - Jaka Waluya; Epun Ningrum; Nandi Nandi; Iwan Setiawan; Amin Amin (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
Character education has become a strategic priority in hi gher education, particularly in teacher education programs, as prospective teachers are expected to demonstrate not only pedagogical competence but also strong moral character and professional integrity. However, empirical evidence regarding the internalization of character values among prospective elementary school teachers remains limited. This study aimed to describe the level of character value internalization among students of the Elementary School Teacher Education (PGSD) Study Program at Universitas Islam 45 Bekasi as preparation for becoming elementary school teachers with noble character. A quantitative descriptive research design was employed involving 120 students selected through a total sampling technique. Data were collected using a character value internalization questionnaire consisting of eight dimensions, namely religiousness, honesty, discipline, responsibility, social care, courtesy, independence, and exemplary behavior as prospective teachers. The collected data were analyzed using descriptive statistics, including percentages and mean scores. The findings revealed that the overall level of character value internalization was categorized as Good, with an average score of 81.78%. Religiousness achieved the highest percentage (85.75%), indicating the successful integration of religious values into students' academic and social lives. Conversely, discipline recorded the lowest percentage (78.20%), suggesting the need for greater emphasis on punctuality, compliance with academic regulations, and responsibility. These findings indicate that the development of character among prospective teachers requires continuous reinforcement through an integrated academic environment, lecturer role modeling, and institutional policies that support character education. This study contributes empirical evidence that may assist higher education institutions in designing sustainable character education programs to prepare competent and morally responsible elementary school teachers.